KINERJA APARATUR SIPIL NEGARA DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BANYUASIN - Austin, Trecy; Ida Royani; Ong Berlian; Abdurrahman Arif (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
This research aims to determine the performance of the State Civil Apparatus of the Banyuasin Regency Education and Culture Service in the distribution of public services in the fields of education and culture, carrying out their responsibilities transparently in the province of South Sumatra. This research uses qualitative research techniques, which not only collect data but also evaluate the data that has been collected, to investigate problems based on real world events. Interviews and direct observation were used to obtain data, which was then compiled and evaluated using qualitative methodology. The study findings show that the potential of ASN in the Banyuasin Regency Education and Culture Office has not been exploited optimally. Various signs point to the fact that some ASN workers are still not making the best use of their time. This is especially true when it comes to efficiency and effectiveness. Absenteeism is another symptom of poor ASN performance. Cost is also a consideration; without APBD, ASN workers cannot carry out their work optimally because they lack the resources they need to do their work. Due to the lack of time efficiency and minimal APBD expenditure, the performance of ASN at the Banyuasin Regency Education and Culture Service is very good but not ideal. If the Banyuasin Regency Education and Culture Office is serious about increasing productivity, it will increase dedication and work discipline, improve working conditions, and provide incentives.